1976
DOI: 10.1056/nejm197604222941703
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Pulmonary Injury Associated with Gold Treatment

Abstract: Two patients had diffuse, reversible pulmonary injury possibly owing to gold sodium thiomalate treatment: a 32-year-old woman with chronic inflammatory arthritis compatible with seronegative rheumatoid arthritis and a 32-year-old man with shoulder arthralgia. The patients had received 420 mg and 325 mg of gold sodium thiomalate, respectively. Cough and dyspnea began in the seventh and fifth weeks of therapy, respectively. In both patients x-ray study showed bilateral pulmonary infiltrates, with no evidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Several patients died be cause of severe hypoxaemias [9][10][11]. Chest roentgenograms show diffuse interstitial infiltrates and air space consolidation in a mixed pattern [3,4,[9][10][11][12]. Pulmonary function tests revealed a restrictive venti latory defect and decreased diffusing ca pacity [3,4,11,12], Pathological changes are non-specific and include interstitial in filtration with plasma cells and lympho cytes, interstitial and alveolar wail fibrosis and intra-alveolar desquamation of mono nuclear cells [3,4,[9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several patients died be cause of severe hypoxaemias [9][10][11]. Chest roentgenograms show diffuse interstitial infiltrates and air space consolidation in a mixed pattern [3,4,[9][10][11][12]. Pulmonary function tests revealed a restrictive venti latory defect and decreased diffusing ca pacity [3,4,11,12], Pathological changes are non-specific and include interstitial in filtration with plasma cells and lympho cytes, interstitial and alveolar wail fibrosis and intra-alveolar desquamation of mono nuclear cells [3,4,[9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Gold salt therapy is an effective treat ment for rheumatoid arthritis [1], although many side effects have been described [2], Since the publication of Winterbauer et al [3], an increasing number of patients with gold-induced pneumonitis were reported 141.…”
mentioning
confidence: 99%
“…Thus it has been described in Japan in asthma patients and in patients whose degenerative joint disease was misdiagnosed as rheumatoid arthritis (1,3,10). Furthermore, fibrosis has resolved on withdrawal of gold only to reappear on re-exposure in two cases (1).…”
Section: Antibodies Against Collagen Have Been Found In Sera From Patmentioning
confidence: 98%
“…However, the case reported by Payne and Connellan in 1980 was diagnosed based on only radiological findings without histological or BAL findings, therefore the diagnosis of EP seems uncertain (14). Yousem Ch e s t c o mp u t e d t o mo g r a p h i c s c a n s h o we d n o n -s e g me n t a l c o n s o l i d a t i o n i n t h e l e f t S 3 a n d i n c r e a s i n g d e n s i t y i n d i f f u s e l u n g f i e l d (16)(17)(18), methotrexate disease modifying anti-rheumatic drugs (DMARDs) (19,20), and nonsteroidal anti-inflammatory drugs (NSAIDs) (21). We had no proof of recurrent EP.…”
Section: It Is Well Known That Ra Complicates Lung Diseases and Some mentioning
confidence: 99%